Grammatical changes in translation as an example of Dale Carnegie's “How to win friends and influence people”. (Eurasian Scientific Herald, 2023)
During this article that grammatical change, which is one of the changes that occur during the translation process, is discussed in detail during the analysis of Dale Carnegie's “How to win friends and influence people”. Below are some examples of grammatical change to better understand this type of change.